2011
DOI: 10.1890/es11-00094.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling artificial light viewed by fledgling seabirds

Abstract: Abstract. Artificial light is increasing in coverage across the surface of our planet, impacting the behavioral ecology of many organisms. Attraction to sources of artificial light is a significant threat to certain fledgling shearwaters, petrels (Procellariidae), and storm-petrels (Hydrobatidae) on their first nocturnal flights to the sea. Disorientation by light can cause these birds to crash into vegetation or manmade structures, potentially resulting in death from physical injury, starvation, dehydration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 20 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…Despite whether pixel values represent the actual light intensity being emitted by lights or the numbers of lights within the pixel area (or both), this satellite layer is suitable for research investigating the threat that light may pose to fledgling seabirds (e.g. Troy et al 2011), as well as the relationship between light and seabird fallout (e.g. Rodrigues et al 2012, Rodriguez et al 2012b), on a large scale.…”
Section: Suitability Of Light Layer Pixel Size For Fallout Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite whether pixel values represent the actual light intensity being emitted by lights or the numbers of lights within the pixel area (or both), this satellite layer is suitable for research investigating the threat that light may pose to fledgling seabirds (e.g. Troy et al 2011), as well as the relationship between light and seabird fallout (e.g. Rodrigues et al 2012, Rodriguez et al 2012b), on a large scale.…”
Section: Suitability Of Light Layer Pixel Size For Fallout Researchmentioning
confidence: 99%
“…In addition, from a stationary perspective (i.e. without considering bird movement), it was recently shown that light could not be viewed from approximately 30% of the island of Kauai (Troy et al 2011), and these dark locations mostly included regions in the interior and northwestern portion of the island where many known Newell's shearwater activity sites are located. Given this additional information concerning viewable light on Kauai, the expected behavior of the species in the absence of light, and the results of this study, it appears likely that many birds could successfully reach the coastline and ocean, where they are then exposed to a range of light intensities emanating from multiple fallout sectors (spanning a large portion of the island) and are more likely to be attracted to sectors with greater light intensities and/or greater densities of light sources.…”
Section: Fledgling Movement and Viewable Lightmentioning
confidence: 99%
“…Light-induced mortality occurs in several gadfly petrels, especially in fledglings [21,22], suggesting that Cape Verde petrels could also be sensitive to light pollution. Indeed, fledglings have been collected in Chã das Caldeiras near light sources in at least three occasions over the last decade (Fogo Natural Park authorities’ personal communication), despite no public lights or infrastructures with important sources of light in the village.…”
Section: Discussionmentioning
confidence: 99%
“…Light-induced mortality is known to occur in other gadfly petrels, especially in fledglings [21,22], pointing out the possibility to also occur in Cape Verde petrels. To identify where conservation actions should be applied in the future to avoid high light pollution levels, and thus reduce the probability of light-induced mortality in the study species, we deployed 15 GPS devices on 9 breeding adults over the chick-rearing period of 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation